My mini book of opposites (Say Publishing Karachi, 2011)
This mini book introduces young learners to the concept of opposites through vibrant illustrations and simple text. Each page features a pair of contrasting concepts, such as big and small, hot and cold, and happy and sad. By exploring these visual and textual cues, children can develop a deeper understanding of opposites and enhance their vocabulary and critical thinking skills. This interactive and engaging book fosters a love of learning and encourages curiosity about the world around them.